USING DOT VOTING TECHNIQUE TO INCREASE THE REPORT TEXT SPEAKING SKILL OF THE ELEVENTH GRADERS OF MAN 1 KOTA MAGELANG IN THE SCHOOL YEAR 2016/2017 - Anita Apriliyani Ningrum; Sukarno Sukarno; M. Malik Al Firdaus (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Speaking is one of the four language skills that is used to express ideas and feelings. The students’ speaking skill of the eleventh graders of MAN 1 Kota Magelang has not achieved the learning target. The objectives of the study are to know how high the use of Dot Voting technique can increase students’ learning motivation in the report text speaking of the eleventh grades of MAN 1 Kota Magelang and to know how great the improvement of the students speaking skill who are taught using Dot Voting technique at the eleventh grades of MAN 1 Kota Magelang is. The type of this research is classroom action research. The subject of the research was class XI-Religion 1 of MAN 1 Kota Magelang. The writer used test and non-test instruments (observation, questionnaire, and documentation) to collect the data. Each cycle consists of planning, observing, acting, and reflecting. In analyzing the data, the writer used quantitative and qualitative data. Based on the writer’s observation and questionnaire, there is some increase of the students’ behavior change after the writer taught using Dot Voting technique in speaking class.